2020
DOI: 10.1021/jasms.9b00087
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Positive Reactant Ions in High Kinetic Energy Ion Mobility Spectrometry (HiKE-IMS) by HiKE-IMS–MS

Abstract: In contrast to classical ion mobility spectrometers (IMS) operating at ambient pressure, the high kinetic energy ion mobility spectrometer (HiKE-IMS) is operated at reduced pressures between 10–40 mbar. In HiKE-IMS, ions are generated in a reaction region before they are separated in a drift region. Due to the operation at reduced pressure, it is possible to reach high reduced electric field strengths up to 120 Td in both the reaction as well as drift region, resulting in a pronounced decrease in chemical cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(92 citation statements)
references
References 38 publications
1
91
0
Order By: Relevance
“…However, when evaluating the ionization pathways in HiKE‐IMS, the reactant ion population inside the reaction region is relevant. As known from previous studies, 21,22 field‐ and moisture‐dependent conversion reactions of O 2 + (H 2 O) n and NO + (H 2 O) n into protonated water clusters H 3 O + (H 2 O) n proceed in the reaction region of the HiKE‐IMS instrument. Thus, the reactant ion population inside the reaction region significantly differs from the population at the end of the reaction region, shown in Figure 1.…”
Section: Resultsmentioning
confidence: 66%
See 4 more Smart Citations
“…However, when evaluating the ionization pathways in HiKE‐IMS, the reactant ion population inside the reaction region is relevant. As known from previous studies, 21,22 field‐ and moisture‐dependent conversion reactions of O 2 + (H 2 O) n and NO + (H 2 O) n into protonated water clusters H 3 O + (H 2 O) n proceed in the reaction region of the HiKE‐IMS instrument. Thus, the reactant ion population inside the reaction region significantly differs from the population at the end of the reaction region, shown in Figure 1.…”
Section: Resultsmentioning
confidence: 66%
“…In previous studies, the prevailing positive reactant ion population in HiKE‐IMS was identified by coupling the HiKE‐IMS instrument to a mass spectrometer, 21 and H 3 O + (H 2 O) n , NO + (H 2 O) n , and O 2 + (H 2 O) n ions were observed. At thermal ion–molecule interaction energies, extensive information is available from selected ion flow tube mass spectrometry studies concerning the reactions of H 3 O + , NO + , and O 2 + with various analyte molecules 25–39 .…”
Section: Ionization Pathways Resulting In the Formation Of Positive Pmentioning
confidence: 99%
See 3 more Smart Citations